ABRI di Tengah Paradoks Sosial - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
Abstract Since the Indonesian Army successfully has increased nation-state economic and welfare level (hand in hand with technocrats and foreign capitals), it has to face a new challenge, that is "discontinuity track". This has been remarked by two socialparadoxes: (I) global competitions that have expressed in severalhumanity issues (human rights democracy, environment) in front of the existence of national development as political legitimation of the New Order rezim